2020
DOI: 10.1096/fj.201902636rr
|View full text |Cite
|
Sign up to set email alerts
|

Toll interacting protein protects bronchial epithelial cells from bleomycin‐induced apoptosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by altered epithelial cell phenotypes, which are associated with myofibroblast accumulation in the lung. Atypical alveolar epithelial cells in IPF express molecular markers of airway epithelium. Polymorphisms within and around Toll interacting protein (TOLLIP) are associated with the susceptibility to IPF and mortality. However, the functional role of TOLLIP in IPF is unknown. Using lung tissues from IPF and control subjects, we showed that expression of TOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…A study investigating TOLLIP expression in lung tissue of IPF patients revealed that the TOLLIP expressing cells were macrophages, alveolar type II, and basal cells. A mechanistic assay using basal cells showed that TOLLIP was able to reduce mitochondrial ROS accumulation following bleomycin-induced mitochondrial damage of basal cells (31). All these data together corroborate the hypothesis of a protective effect of TOLLIP in several cell populations against oxidative damage and brosis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A study investigating TOLLIP expression in lung tissue of IPF patients revealed that the TOLLIP expressing cells were macrophages, alveolar type II, and basal cells. A mechanistic assay using basal cells showed that TOLLIP was able to reduce mitochondrial ROS accumulation following bleomycin-induced mitochondrial damage of basal cells (31). All these data together corroborate the hypothesis of a protective effect of TOLLIP in several cell populations against oxidative damage and brosis.…”
Section: Discussionsupporting
confidence: 76%
“…The importance of TOLLIP in IPF is emphasized by the relationship between biological impact and potential disease outcome. Besides the well-known role in in ammation and autoimmunity by enhancing signaling pathways associated with IL-1β, TNF-a, IFN-b, IL-13, toll-like receptor (TLR) (29) and autophagy (30), a recent study revealed that TOLLIP protects bronchial epithelial cells from bleomycininduced apoptosis (31). A study investigating TOLLIP expression in lung tissue of IPF patients revealed that the TOLLIP expressing cells were macrophages, alveolar type II, and basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating TOLLIP expression in lung tissue of IPF patients revealed that the TOLLIP expressing cells were macrophages, alveolar type II, and basal cells. A mechanistic assay using basal cells showed that TOLLIP was able to reduce mitochondrial ROS accumulation following bleomycin-induced mitochondrial damage of basal cells (30). All these data together corroborate the hypothesis of a protective effect of TOLLIP in several cell populations against oxidative damage and brosis.…”
Section: Discussionsupporting
confidence: 76%
“…The importance of TOLLIP in IPF is emphasized by the relationship between biological impact and potential disease outcome. Besides the well-known role in in ammation and autoimmunity by enhancing signaling pathways associated with IL-1β, TNF-a, IFN-b, IL-13, toll-like receptor (TLR) (28) and autophagy (29), a recent study revealed that TOLLIP protects bronchial epithelial cells from bleomycininduced apoptosis (30). A study investigating TOLLIP expression in lung tissue of IPF patients revealed that the TOLLIP expressing cells were macrophages, alveolar type II, and basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Regardless, TOLLIP has been shown to suppress TLR activation, particularly TLR2 and TLR4, by inhibiting IL-1 receptor-associated kinase (IRAK) phosphorylation. [77][78][79][80] Both TLR2 and TLR4 activation occur in response to many different microbial signals and have been shown to be elevated in IPF epithelia, possibly due to chronic exposure to pathogenic microbes. 81 Reduced TOLLIP expression has been shown to increase proinflammatory cytokine (IL-6 and TNF) production by macrophages after TLR stimulation.…”
Section: Pro-fibrotic Tlr Signalingmentioning
confidence: 99%